PERISTIWA TINDAK KOMUNIKATIF SINAMOT PADA PERNIKAHAN ADAT BATAK TOBA KELUARGA SILITONGA - BR Silitonga, Irma; Fitriana Poerana, Ana; Oktariani Lubis, Fardiah (Penerbit Lafadz Jaya, 2025)
This study examines the communicative acts in the Sinamot tradition during Toba Batak traditional weddings, particularly within the Silitonga family. The Sinamot tradition, often perceived as merely an economic transaction, is actually a symbolic interaction process imbued with cultural, social, and kinship identity meanings. Using Herbert Blumer's Symbolic Interaction Theory and Dell Hymes's Communication Ethnography Approach (SPEAKING), this study aims to uncover the symbolic meaning and role of Marhata Sinamot and the communication patterns in each stage of the Marhata Sinamot negotiations. The method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The results of the study indicate that the Sinamot event is not only a forum for negotiation, but also a means of forming collective identity and preserving traditional values through the symbols and language used by the communicators. Speech acts in this process reflect the social structure and power relations between the parties involved, as well as being a reflection of the dynamics of Toba Batak culture.